Adsorption isotherm, kinetics and thermodynamic of acid blue and basic blue dyes onto activated charcoal. (September 2020) - Ali, Farman; Ali, Nisar; Bibi, Iram; Said, Amir; Nawaz, Shahid; Ali, Zarshad; Salman, Syed Muhammad; Iqbal, Hafiz M.N.; Bilal, Muhammad
Abstract: Adsorption of Basic blue and Acid blue from aqueous solution onto powder activated charcoal (PAC) has been investigated. The effect of adsorbent dosage, contact time, temperature, and pH was evaluated. Adsorption data obtained at different temperatures revealed irreversible adsorption that decreased with the increase in temperature. It was also noted that adsorption of acid blue on activated charcoal decreases with an increase in the pH while that of increases with pH in case of basic blue. The adsorption isotherms at different temperatures were found to be of L-type. Adsorption data were fitted to Freundlich and Langmuir isotherms, and various adsorption parameters have been calculated. The thermodynamic parameters, such as ΔG, ΔH, and ΔS, were also computed. Both Basic blue and Acid blue are found to be chemisorbed on activated charcoal. The kinetic modeling of the adsorption process for removal of the resorcinol was evaluated. Precisely, the pseudo-second-order kinetic model was followed more closely compared to the pseudo-first-order model. Results showed that the maximum adsorption capacity was 151.3 mg ​g −1 for a dye concentration of basic blue (1.5 ​ppm) and acid blue (2.5 ​ppm) using an adsorbent dosage of 10 mg at 55 ​°C. In conclusion, the powder activated charcoal may display a high potential for the treatment of dye-containing wastewater.